Improving Students' Vocabulary Mastery and Listening Skills Using Bilingual Posters Translated Lyrics - Nur Rohman, Ana Bela Safitri; Sujatmiko, Sujatmiko (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
This research aims to: 1) To know the translation techniques used in translating the songs